2009
DOI: 10.1136/sti.2008.034538
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients infected with common Neisseria gonorrhoeae NG-MAST sequence type strains presenting at the Edinburgh genitourinary medicine clinic

Abstract: There was a trend towards significance when comparing the risks of carriage/contact with HIV between different sequence type clusters. Further research is therefore warranted to determine if NG-MAST data can be used to help identify high-risk sexual networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
1
10
0
2
Order By: Relevance
“…As shown previously5 16 there was high concordance (83%) between NG-MAST STs and named sexual contacts demonstrating again the application of NG-MAST as a confirmatory tool with contact tracing. However, the use of NG-MAST alone in social network analysis does have limitations as STI networks are not closed and inference on which network or cluster an individual belongs to should be taken with great care.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As shown previously5 16 there was high concordance (83%) between NG-MAST STs and named sexual contacts demonstrating again the application of NG-MAST as a confirmatory tool with contact tracing. However, the use of NG-MAST alone in social network analysis does have limitations as STI networks are not closed and inference on which network or cluster an individual belongs to should be taken with great care.…”
Section: Discussionsupporting
confidence: 75%
“…A study of the gonococcal population in patients attending an STI clinic in Edinburgh also showed STs 4, 64, 210 and 225 were MSM-associated 16. STs 147, 225 and 359 have been reported in MSM in other European countries,17–19 although the Scottish study and another conducted in Sweden suggested that ST 147 can be observed in a significant proportion of heterosexual patients also 16 20. To our knowledge, the association between MSM and STs 1634, 960 and 597 has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over one third of studies used isolates collected in the UK (37%; 18/49), 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 from consecutive patients during the study time period (35%; 17/49), 11 , 14 , 15 , 16 , 17 , 21 , 22 , 24 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 or limited inclusion of isolates to those known to be resistant to a specific antimicrobial (35%; 17/49). 9 , 10 , 13 , 18 , 19 , 20 , 23 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 The number of isolates sampled ranged from six to 3326, with studies covering a time period of less than six months to nine years (Supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…К настоящему времени имеются сообщения: -о возможности использования данных NG-MAST для изучения штаммов N. gonorrhoeae, циркулирующих в определенном географическом регионе [96]; -об ассоциациях отдельных кластеров штам-мов N. gonorrhoeae, установленных методом NG-MAST, с эпидемиологически значимыми группами пациентов, в частности, с МСМ [97]; -о возможностях использования метода NG-MAST и других методов ДНК-типирования для изуче-ния закономерностей распространения гонококковой инфекции среди половых партнеров [98][99][100][101][102];…”
Section: современные подходы к эпидемиологическому наблюдению над расunclassified